Healthy life behavior and risky behavior in child labor in Pandang Village, Makassar - Tuhelelu, Ghifari M. Nuh; Mallapiang, Fatmawaty; Ibrahim, Hasbi (Unified Health Critical Research, 2025)
The phenomenon of child labor often appears in the midst of urban communities, namely around 2.1 million child workers, including the children of street vendors. This study aims to determine the Healthy Lifestyle and Risky Behavior of Child Labor (Street vendor) in Pandang Village, Panakukang District, Makassar City. The type of research used is quantitative with a descriptive-observational approach. The population in this study were all child workers who worked as hawkers in Pandang Village, Panakkukang District, Makassar City. The sample in this study amounted to 37 respondents. The data were analyzed using Validity, and Reliability Test. The results showed that the eating and drinking behavior of street vendors based on knowledge was 78%, attitude was 59%, and for actions was 70%, for personal hygiene behavior, the level of knowledge was 78%, attitude was 54%, and action was 59%. , Then for risky behavior, the level of knowledge is 62%, attitude is 59%, and action is 59%. It is expected that child workers (hawkers) do not work excessively or more than 4 hours per day, and pay more attention to their health and education conditions.